Asymmetric syntheses of 2,5-dideoxy-2,5-imino-d-glucitol [(+)-DGDP] and 1,2,5-trideoxy-1-amino-2,5-imino-d-glucitol [(+)-ADGDP] - Davies, S; Figuccia, A; Fletcher, A; Roberts, P; Thomson, J (Elsevier, 2014)
The asymmetric syntheses of 2,5-dideoxy-2,5-imino-d-glucitol [(+)-DGDP] and 1,2,5-trideoxy-1-amino-2,5-imino-d-glucitol [(+)-ADGDP] were achieved via the ring-closing iodoamination of an enantiopure bishomoallylic amine, followed by functionalisation of the resultant iodomethyl substituted pyrrolidine. In the case of (+)-DGDP, formation of the corresponding aziridinium ion followed by regioselective ring-opening with H2O gave the desired hydroxymethyl substituted pyrrolidine as a single diastereoisomer (>99:1 dr), with subsequent deprotection giving (+)-DGDP in good yield. Whereas in the case of (+)-ADGDP, displacement of iodide with NaN3 proved to be optimal, giving (+)-ADGDP in good yield after reduction and deprotection. © 2014 Elsevier Ltd. All rights reserved.